(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2026)
Xantolis tomentosa (Roxb.) Raf. is an ethnomedicinal plant traditionally used for treating inflammatory and infectious disorders. In the current research, Response Surface Methodology (RSM) was used to optimize the extraction of bioactive compounds from X. tomentosa leaves. A Box–Behnken Design (BBD) was applied to evaluate the effects of solvent concentration (40–80%), extraction temperature (40–70°C), and extraction time (20–60 min) on phytochemical yield and biological activity. The optimized extraction conditions yielded elevated levels of total flavonoids (11.8 mg/g), total phenolics (0.98 mg/g), and total terpenoids (0.48 mg/g). The extract demonstrated strong antioxidant activity, with DPPH radical scavenging inhibition ≥ 83.2%, along with significant antimicrobial activity (maximum inhibition zone: 20.14 mm). GC–MS analysis identified multiple compounds with potential biological activity, supporting the observed antioxidant and antimicrobial properties. These findings demonstrate that statistically optimized extraction significantly enhances the bioactivity of X. tomentosa and provide scientific validation for its traditional medicinal applications.